STUDY OF SUFI MAQĀMĀT ON THE INDONESIAN TAFSIR WEBSITE: A STUDY OF THE TANWIR.ID AND TAFSIRALQURAN.ID WEBSITES - Alkaf, Ali (Universitas Nurul Jadid, 2023)
This study aims to analyze maqamat studies on two well-known commentary websites in Indonesia, namely Tafsiralquran.id and Tanwir.id. The research was carried out using the method of comparative analysis, involving the collection of data from the two websites. In the early stages, the researcher explored and selected materials related to maqamat studies. Then, the collected data is analyzed qualitatively, taking into account the use of maqamat, related explanations and interpretations, as well as differences or similarities between the two. The research model that the author uses uses a Library research methodology. Namely research that is descriptive in nature and compiles data in the form of verbal narratives, not with numbers and tends to be narrative. In conclusion, this study shows the difference in approach between Tafsiralquran.id and Tanwir.id in presenting maqamat studies. Tafsiralquran.id prioritizes a traditional approach by referring to classical interpretations, while Tanwir.id takes a more contemporary approach by paying attention to the context and current issues. These findings provide valuable insights for web interpreters in selecting sources that suit their needs and preferences.